Electrical characterization of amorphous LiAlO2 thin films deposited by atomic layer deposition. Issue 65 (23rd June 2016) - Hu, Yang; Ruud, Amund; Miikkulainen, Ville; Norby, Truls; Nilsen, Ola; Fjellvåg, Helmer
Abstract : Comparison of in-plane and cross-plane conductivity on ALD-deposited LiAlO2 thin films. Abstract : LiAlO2 thin films deposited by atomic layer deposition (ALD) have a potential application as an electrolyte in three-dimensional (3D) all-solid-state microbatteries. In this study, Li-ion conductivity of such films is investigated by both in-plane and cross-plane methods. LiAlO2 thin films with a Li composition of [Li]/([Li] + [Al]) = 0.46 and an amorphous structure were grown by ALD with thicknesses of 90, 160 and 235 nm on different substrates. The electrical characterization was conducted by impedance spectroscopy using inert electrodes over a temperature range of 25–200 °C in an inert atmosphere. In-plane conductivities were obtained from films on insulating sapphire substrates, whereas cross-plane conductivities were measured from films on conducting titanium substrates. For the first time, comparison of the in-plane and cross-plane conductivities in these ALD LiAlO2 films has been achieved. More comparable results are obtained using a cross-plane method, whereas in-plane conductivity measurements demonstrate a considerable thickness-dependence with thinner film thickness. The room-temperature conductivity of the LiAlO2 films has been determined to be in the order of 10 −10 S cm −1 with an activation energy of ca. 0.8 eV.